Findings from the National Memory Screening Day Program. Issue 2 (30th January 2015) - Bayley, Peter J.; Kong, Jennifer Y.; Mendiondo, Marta; Lazzeroni, Laura C.; Borson, Soo; Buschke, Herman; Dean, Margaret; Fillit, Howard; Frank, Lori; Schmitt, Frederick A.; Peschin, Susan; Finkel, Sanford; et al.
<x xml:space="preserve">Abstract</x> Objectives To report experience with a large, nation‐wide public memory screening program. Design Descriptive study of community‐dwelling elderly adults. Setting Local community sites (48 sites agreed to provide data) throughout the United States participating in National Memory Screening Day in November 2010. Participants Of 4, 369 reported participants, 3, 064 had complete data records and are included in this report. Measurements Participants completed a questionnaire that included basic demographic information and a question about subjective memory concerns. Each site selected one of seven validated cognitive screening tests: Mini‐Cog, General Practitioner assessment of Cognition, Memory Impairment Screen, Kokmen Short Test of Mental Status, Mini‐Mental State Examination, Montreal Cognitive Assessment, Saint Louis University Mental Status Examination. Results Overall, 11.7% failed one of the seven screening tests. As expected, failure rates were higher in older and less‐educated participants (P's < .05). Subjective memory concerns were associated with a 40% greater failure rate for persons of similar age and education but no memory concerns (odds ratio = 1.4, 95% confidence interval = 1.07–1.78), although only 11.9% of those who reported memory concerns (75% of all participants) had detectible memory problems. Conclusion Screening for cognitive impairment in community settings yielded results consistent with expected effects of age and education. The event attracted a large proportion of individuals with memory concerns; 88.1% were told that they did not have memory problems detectible with the tests used. Further studies are needed to assess how participants respond to and use screening information, whether this information ultimately influences decision‐making or outcomes, and whether memory screening programs outside healthcare settings have public health value.